PERLINDUNGAN KONSUMEN TERHADAP JUAL BELI COKLAT SILVER QUEEN BLOCK DALAM PERSPEKTIF HUKUM EKONOMI SYARIAH - Dewi Amrom Musta’idah; Yumna Hasna’ Azizah; Doli Witro; Dena Ayu; Muhamad Izazi Nurjaman (Al-Amwal : Journal of Islamic Economic Law, 2021)
Buying and selling silver queen block chocolate is currently in great demand by consumers. However, there are several problems in buying and selling chocolate in practice, including the lack and incompatibility of information about the chocolate being sold. This study highlights consumer protection for buying and selling silver queen block products and the responsibility of business actors to buy and sell silver queen block products in the marketplace. The research, including normative juridical research, is legal research using a literature review. The study results show that consumer protection against buying and selling silver queen block chocolate is in the form of the right for consumers to know the factual information about the purchased silver queen block chocolate. Meanwhile, if the consumer feels aggrieved as a result of consuming the chocolate, the buyer receives compensation from the seller in the form of a refund and replacement of goods equivalent to or following the value of the goods returned, this regulation is following applicable law with Article 19 of Law Number 8 of 1999 concerning Consumer Protection. When viewed from the perspective of sharia economic law, the concept of khiyar in online buying and selling is able to provide protection for buyers when the goods ordered are not in accordance with expectations and the application of the khiyar concept in practice will create transactions that provide benefits and avoid harm.